ANALISIS STUDI PERAN BAITUL MAAL WAT TAMWIL DALAM PENINGKATAN INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN KUNINGAN - Sujata, Tatang (Jurnal Ilmiah Dozen Globalindo, 2021)
Today's problems, problems regarding the achievement of human development have become the attention of government administrators. The priority of service partnerships is especially for small businesses that do not have banking access and those who do not have business access. Baitul Maal Wat Tamwil (BMT) in Kuningan Regency which also plays a role in the Community Development program. The research method used in this study is a qualitative method (qualitative research). Baitul Maal Wat Tamwil (BMT) is a business organization that also plays a social role. The social role of BMT is seen in the definition of baitul maal, while the business role of BMT is seen in the definition of baitul tamwil. As a social institution, baitul maal has a function and role with the Amil Zakat Institution (LAZ). Therefore, this baitul maal must support in order to be able to play a professional role in becoming an established LAZ. This function includes at least efforts based on zakat, infaq, shadaqah, waqf and other sources of social funds. an increase in HDI as a manifestation of human development can be interpreted as an increase in the ability to expand choices (enlarge people's choices).